Physical habitat assessment for dominant freshwater fish species in Galas River Basin, Kelantan, Malaysia - Aini, Norfadilah (2016)
This study elucidates the relationship of different flow regimes as a function of physical microhabitat changes, besides determining the optimum flow required to maintain suitable habitat for three target freshwater fish species. These species namely Mystacoleucus obtusirostris (Sia), Barbonymus schwanenfeldii (Lampam sungai) and Cyclocheilichthys apogon (Temperas) were selected based on five criteria; most sensitive, transferability, economic and social interest, vulnerability and extent available information. The issue need to be tackle in this study is river basin significantly causes alteration to the flow regime as well as deterioration of water quality, which subsequently causes alteration to the fish population in terms of its wellbeing and population growth. Any alteration by human activities put the integrity of the river ecosystem at risk in study area especially sedimentation problem. The increasing on human activities gives negative impact to the freshwater fish in the river. Moreover, it more challenge when these freshwater fishes are regarded as an economic source to the local residents along the river. Regarding this issue, hydrological index method (7Q35 analysis) and physical habitat simulation (Physical Habitat Simulation Model) are adopted for an environmental flow assessment. Besides that, in this study is analysing the hydrological factor that affected the flow regimes for example water quality analysis, land use changes and soil loss. From the calculation of minimum annual mean (MAM) has recorded 7-day low flow for every 50-year period is about 5.786 m3/s for low flow event. Otherwise, from the simulation water levels need to cater for these three freshwater fish species to survive in certain reach along the Galas River species are at 0.40 m (Mystacoleucus obtusirostris), 0.60 m (Barbonymus schwanenfeldii) and 0.40 m (Cyclocheilichthys apogon). The recommended flow regimes in the study area are based on the surface area of usable habitat calculation for three targeted species respectively is at 6.42 m3/s,10.89 m3/s and 7.26 m3/s. Lastly, the recommended flow regime for the Galas River is 10.89 m3/s and it derived for this study as one of propose input to the assessment of alternative stream flow management in the future.